Feasibility Analysis of Assessment Program and Professional Certification in Ensuring and Maintaining Employess Competence to Increase Value of PT Krakatau Steel (Persero) Tbk - Kunariadi, Didik Sugeng; Soekarno, Subiakto (The Indonesian Journal of Business Administration, 2013)
PT Krakatau Steel (Persero) Tbk is currently faced with the situation of business conditions characterized by raw material prices continue to rise and operational costs wastage resulting in increased cost of goods sold thus decrease the profitability of the company. Many factors can cause these problems, one of it is determined by the competence and professionalism of the employees, especially those directly related to the production line. HR competencies problems caused by the company does not have a model to ensure and maintain the specific competencies of employees who refer to job competence standards through the implementation of the competency assessment to give recognition to the professional certification/ allowances are integrated so that has an impact on the operating cost savings program (increasing the value of the company) as well as improvement specific competencies program of employees through training programs. Based on the analysis of the questionnaire influences the relationship between professional certification and organizational performance that is filled by the managements of the company's management indicated that professional certification and significantly positively related to organizational performance.